2009
DOI: 10.2337/dc08-1144
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40, a Marker of Inflammation and Endothelial Dysfunction, Is Elevated in Patients With Type 1 Diabetes and Increases With Levels of Albuminuria

Abstract: OBJECTIVE -The inflammation marker YKL-40 is elevated in patients with type 2 diabetes and is associated with atherosclerosis and increased cardiovascular mortality. In the present study, YKL-40 levels were examined in patients with type 1 diabetes with increasing levels of albuminuria, known to be associated with an increased risk of cardiovascular disease.RESEARCH DESIGN AND METHODS -A total of 149 patients with type 1 diabetes attending Steno Diabetes Center were examined: 58 had normoalbuminuria (urinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
103
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 26 publications
17
103
5
Order By: Relevance
“…In line with some other studies (19,21), we found a higher YKL-40 serum level in the group of T1D patients. Such elevation has also been reported in pre-diabetic (13) as well as in type 2 diabetic patients (13,20).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with some other studies (19,21), we found a higher YKL-40 serum level in the group of T1D patients. Such elevation has also been reported in pre-diabetic (13) as well as in type 2 diabetic patients (13,20).…”
Section: Discussionsupporting
confidence: 93%
“…A significant correlation between YKL-40 plasma levels and age has been a matter of agreement (19,20,22,23,25,26,(28)(29)(30) or disagreement (14, 31-34) (like ours) in different studies. Such pros (23,24,35) (like ours) and cons (13,14,19,27) issues are also true in the case of the significant correlation between YKL-40 plasma levels and BMI.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations